From Bean to Brand: Innovative Strategies for Enhancing the Economic Value of Coffee in Watutau Village, Lore Peore Subdistrict, Poso Regency, Central Sulawesi Province - Indra Setiawan; Syamsul Bahri Dg. Parani; Maskuri Sutomo; Erwan Sastrawan Farid (The Journal of Financial, Accounting, and Economics, 2024)
Indonesia is one of the largest coffee producers in the world, but the country's contribution to global coffee exports has declined significantly, mainly due to the low added value of coffee products that are still sold in raw form. Meanwhile, domestic coffee consumption continues to increase, providing opportunities for Micro, Small, and Medium Enterprises (MSMEs) to develop coffee products with higher added value. This study focuses on Watutau Village, which is famous for its high-quality coffee, but has not been optimal in utilizing this potential. The majority of coffee farmers in Watutau Village still sell raw coffee beans, which results in low product sales value and farmer welfare. Therefore, this study explores the potential for innovation in processing, packaging, and branding to increase the competitiveness and income of coffee MSMEs in the village. Through a qualitative approach and case studies, this study identifies the challenges faced by farmers and MSMEs in increasing the added value of coffee, and develops innovative strategies involving post-harvest processing, attractive packaging, and building a strong brand identity. This study also aims to strengthen the local coffee MSME sector and increase farmers' income. The results of the study are expected to provide theoretical contributions in the field of entrepreneurship and agribusiness product innovation, as well as practical guidance for business actors and local governments in designing economic empowerment programs based on local potential.